Biomimetic Cubane‐Type Manganese Complex: Structurally Inspired by Photosystem II. (10th August 2021) - Kim, Jennifer Juhyun; Kim, Namseok; Yoon, Sungho
Abstract : A biomimetic system comprising a cubane‐type tetranuclear complex with a [Mn4 O4 ] center similar to the core of the oxygen‐evolving complex (OEC) of photosystem II (PSII), which is responsible for producing molecular oxygen, was synthesized from bulky carboxylate ligands and manganese by an expedient process. The synergistic effect of the exterior ligands attached to the core and the interatomic interactions led to a cubane‐type morphology. This study lays the foundation for further study of metallic complexes analogous to biotic matter and contributes to structural knowledge of the second coordination sphere. In addition, the findings may shed light on the mechanism of oxygen evolution during photosynthesis. Abstract : The successfully synthesized cubane‐type manganese complex, [Mn4 (μ‐OMe)4 (O2 CAr Tol )4 (MeOH)8 ], is analogous to the oxygen‐evolving complex (OEC) in photosystem II. Its biomimetic feature has critical value that may clarify the importance of manganese in the process of oxygen evolution.